EU merger control in differentiated product industries - Franco Mariuzzo; Patrick Paul Walsh; Ciara Whelan (Center for Economic Studies and ifo Institute (CESifo), 2004)
EU Merger Control Regulation No 4064/89 tended to rely on a dominance test, based on the market share of undertakings, to indicate the level and potential changes in market power. The use of such in differentiated product industries is questionable. New EC Merger Regulation No 139/2004 introduces a substantive test to ensure that all post-merger scenarios posing a threat to competition, even amongst small undertakings, are detected. We propose the use of a simple structural approach to undertake a substantive test. We illustrate our point over 28 periods, 178 products (13 companies), for Retail Carbonated Soft Drinks. We estimate company (product) mark-ups using a 'simple? Nested Logit model, Berry (1994) and a more 'sophisticated? model, Berry, Levinsohn and Pakes (1995). While the dominance test may fail to identify damaging mergers in differentiated products industries, this technique will not.
Keywords: L40; L81; L25; L11; K2; 330; market shares; market power; differentiated products industries; mergers; Fusionskontrolle; Produktdifferenzierung; Marktmacht; Relevanter Markt; EU-Staaten